On a non-dissipative Kirchhoff viscoelastic problem - N. Tatar (Հայաստանի ԳԱԱ)
In this paper we consider a Kirchhoff type viscoelastic problem, and prove uniform stability of the system.
Keywords: Mathematics; Science